Biological processes in gray forestal soil under winter wheat by ecologized fertilizing systems - А. О. DUBYTSKA; О. Y. KACHMAR; О. V. VAVRYNOVYCH; О. L. DUBYTSKYI (Передгірне та гірське землеробство і тваринництво)
The results of effectiveness studies of the ecologized fertilizers systems use (EFS), arranged on the basis of the optimal rate of mineral fertilizers (N60P90K90), treatment of plants with the biostimulator (BS) terra-sorb with addition of humus or microbiological fertilizer (HF – eco-impulse or MF – eco-soil, respectively) on biological processes in the soil under winter wheat are presented. The studies were carried out in 2018–2020 in the stationary experiment on productivity of short crop rotations on the experimental field of the Institute of Agriculture of Carpathian region NAAS of Ukraine. The soil of the experimental field is gray forestal surface-gleyed, in which biochemical (enzymatic) activity was diagnosed, in particular, cellulolytic, proteolytic, dehydrogenase and content of labile (mobile) organic matter was determined taking into account yield of winter wheat. Using fertilizers systems N60P90K90 or N60P90K90 + BS, soil's cellulolytic and proteolytic activity increased markedly relative to the control. The highest increase level in destructive ability of corresponding soil hydrolases among the EFSs used was provided by the factor of organic components added to the soil (HF or MF on the background of N60P90K90 + BS). Under such conditions, cellulolytic and proteolytic activities in the soil were 34.80–37.70 and 11.90–11.40%, respectively. Under conditions of N60P90K90, N60P90K90 + BS, a clear decrease of the dehydrogenase activity in the soil by 13.12–19.67% was noted, while after the addition of HF or MF there was a trend towards increase of this activity (+4.92–11.48%) relative to control. The applied fertilizers systems led to increase of the accumulation levels of labile humus carbon in the soil by 13.35–26.46% compared with the control variant. Introduction of HF or MF together with BS on the mineral background, provided the highest content of carbon of the mobile organic matter (588.4 and 561.7 mg/100 g of soil, respectively). Such an integrated application of elements of the ecologization (BS – influence on the plant, HF or MF – effect on the soil) was the most effective in dirrection of improving winter wheat productivity. The yield of the studied crop on the background of N60P90K90 was 5.16 t/ha, whereas after addition of ecologization elements (BS, BS + HF, BS + MF), the values of this indicator experienced an increase by 3.00–9.65% in relation to the variant N60P90K90. The results obtained make it possible to form separate elements of the scientific foundations, that are necessary for development of ways and methods of improving the biological state of soils, obtaining high and sustainable crop yields.